The use of sodium pyruvate and sodium hydroxide to increase the number of colonies and coloured antigen yield of Mycoplasma gallisepticum - Soeripto . (Indonesian Center for Animal Research and Development (ICARD), 1997)
A trial to increase the number of colonies and coloured antigen yield of Mycoplasma gallisepticum in mycoplasma broth medium was conducted by comparing the use of normal medium, medium with sodium pyruvate and medium with sodium hydroxide. The result showed that medium with §odium pyruvate had increased the number of colonies and antigen yield and was highly significant different (P< 0.01) compared to both normal medium and medium with sodium hydroxide. Medium with sodium hydroxide produced the number of colonies and antigen yield lower than medium with sodium pyruvate, but higher and was highly significant different (P< 0.01) compared to the normalmedium. Key words: Sodium pyruvate, sodium hydroxide, Mycoplasma gallisepticum antigen